Estudo da kombucha e scoby: análise bibliométrica, de perfil nutricional e obtenção de película por desidratação - Melo, Letícia Maria de (2024)
Kombucha is an ancient drink, traditionally obtained by fermenting sweetened black tea from the metabolism of Symbiotic Culture of Bacteria and Yeasts (SCOBY). At the end of fermentation, two products of interest to the industry are created: the drink with high commercial interest due to its nutritional composition and the SCOBY rich in nutrients and with potential application in several areas. The objective of this work was to carry out two chapters of literature review, on Kombucha and SCOBY, covering a historical overview and current perspectives, an overview of the nutritional profile, sensory aspects and post-biotic potential, as well as developing an edible biofilm, incorporated with SCOBY. with seedless passion fruit pulp, using different drying methods (lyophilization, convective drying- SC and Cast tape drying- CTD) and analyzing the influence of temperature and material thickness. As evidenced in chapter 1, the first records of Kombucha occurred since 1928, but a significant increase has occurred in the last ten years. Through the map of occurrence of keywords using kombucha, the association of kombucha with functional nutrition and antioxidant and antimicrobial activities was noticed, confirming its nutraceutical potential. The term SCOBY, on the other hand, was characterized as a more recent field of research and associated with the production of bacterial cellulose (BC). In the second chapter, the nutritional characteristics of kombucha were discussed. Regarding the macronutrient content, the drink is mainly composed of carbohydrates (sucrose, glucose and fructose), has a low concentration of proteins and no lipids. While the SCOBY is composed of carbohydrates (fibers from CB), proteins and lipids, the latter may be the result of the presence of microbial cells that make up the SCOBY. Furthermore, the products contain a wide variety of vitamins (vitamin C and B complex), minerals (iron, zinc, magnesium), phenolic compounds, flavonoids and organic acids, with emphasis on acetic, gluconic and glucuronic acid. Furthermore, it reveals to be a product with post- biotic potential, as it contains compounds such as enzymes, short-chain fatty acids, vitamins and minerals, D-saccharic acid 1,4-lactone (DSL), organic acids and bacterial cellulose. The third chapter demonstrated that the best drying conditions for the SCOBY biofilm with passion fruit in the CTD was 75 ºC and 4 mm, and in this condition the humidity reduced to 0.186 (b.s) after 90 minutes. In contrast, for convective drying (65 ºC and 4 mm), the humidity reached 0.18 (b.s) with a process time of 300 minutes. The biofilm is composed of carbohydrates (3.87%), ash (0.82%), crude fiber (0.75%), with lower concentrations of lipids (0.52%) and proteins (0.43%), in addition to bioactive compounds such as phenolics (8145.51 to 12355.95 mg GAE/g) and flavonoids (13.96 to 165.55 mg rutin/100g). In summary, the results indicate that the surplus SCOBY from kombucha, used as raw material for the production of an edible biofilm through SC and CTD, is a promising alternative for the reuse of this kombucha residue.